Low load numerical simulation in combustion optimization of a 1 000 MW coal-fired boiler at deep peak load regulation - Pengtai GU; Xiangfeng JIANG (Meitan xuebao)
Low load operation is usually involved during response for deep peak load regulation for large-scale coal-fired boilers, which requires overcoming problems such as the lowering of boiler combustion stability, hydrodynamic safety, and flue gas inlet temperature of SCR denitrification, while low load boiler combustion stability is the most common problem faced by the power plants amongst the aforementioned problems. During low load working condition, temperature of main combustion region decreases, amounts of coal and airflow velocity decrease as well, causing the worsening of tangential combustion stability. The improper configuration of operating parameters and regimes may lead to serious accidents such as furnace flameout. For the problem of lowering boiler combustion instability during low load, under the prerequisite of no additional fee for technical overhaul, the impact of operation parameters and regimes on furnace combustion during 20% low working load of a 1000 MW tower-type boiler is analyzed. A coupled numerical simulation model of furnace combustion and working medium heat transfer in water wall is established in Fluent. Heat load is transferred to water wall by UDF. Different characteristics of water wall working medium in single-phase flow and two-phase flow, as well as heat transfer deterioration in two-phase flow, are taken into consideration, which are subsequently transferred to furnace combustion side for further computation. Iteration is carried out until deviation meets requirement. The problem of lowered computational accuracy caused by simplifying computation procedure and boundary condition for heat transfer of surfaces is resolved. The impact of key factors such as primary air velocity, mill combination, and secondary air distribution on combustion stability is analyzed from the prospective of flue gas temperature along furnace height, tangential combustion configuration, ignition condition along axial direction of coal nozzle, and NOx discharge. According to the results, secondary air distribution has the most significant influence on furnace combustion, followed by secondary air distribution, while mill combination has the least impact, relatively. Compared to inverted-tower-type secondary air distribution, adopting tower-type secondary air distribution increases the temperature of primary air nozzle horizontal section by 174 K and increases the NOx concentration at boiler outlet from 343.9 mg/m3 to 382.5 mg/m3. During tower-type secondary air distribution, oxygen supply is sufficient in main combustion region with fierce combustion, forming comparatively strong oxidizing atmosphere. Large-scale crown-shaped high temperature region is formed in main combustion region, decreasing the tendency of temperature drop from outer area to inner area of tangential combustion, while coal ignition condition is relatively lightly influenced. The computational results could guide combustion optimization for large-scale boilers at low load during deep peak load regulation.